The Banker - Financial Times (London Financial Times, 2004)
​IFC page: "The Banker provides economic and financial intelligence for the world's financial sector and has built a reputation for objective and incisive reporting. The Banker strives to stimulate and inform, offering an unparalleled outlook with a wide range of news, features, analysis and interviews, and in-depth coverage of all the key issues facing the financial sector. The Banker combines in-depth regional and country coverage with reports on: Markets: Capital markets, derivatives & structured products, infrastructure & project finance and Islamic finance. Banking, regulation and risk: Regulation, retail banking, wholesale banking, private banking, management and governance issues. Transactions and technology: trading, trade finance, securities services, cash management and transaction bankers Data: International financial centres, trends and rankings, including the Top 1000 World Banks"
Some issues have supplements Vol. 148 (1998) #864 and vol. 154 (2004) # 948 are also available at the library
Keywords: Banks and Banking; BANKING; Bankers; FINANCE; INTERNATIONAL FINANCE; PERIODICALS